Queer Aging in North American Fiction - Hess, Linda M. author. aut Link
XI, 240 p.
Keywords: Exploring representations of queer aging in North American fiction, this book illuminates a rich yet previously unheeded intersection within American culture. At a time when older LGBTQ persons gradually gain visibility in gerontological studies and in the media, this work provides a critical perspective concerned with the ways in which the narratives and images we have at our disposal shape our realities. Each chapter shines a spotlight on a significant work of queer fiction, beginning with post-WWII novels and ending with filmic representations of the 2010s, exploring narratives as both reflections and agents of broader cultural negotiations concerning queer sexuality and aging. As a result, the book not only redresses queer aging’s history of invisibility, but also reveals narratives of queer aging to be particularly apt in casting new light on the ways in which growing older is perceived and conceptualized in North American culture. .